Social Policy Strategy in an Effort to Minimize Crime in East Java - Sukmana, Hendra; Mursyidah, Lailul; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to describe social policy strategies that can be applied in an effort to minimize the crime rate in East Java and to describe obstacles in implementing social policy strategies in an effort to minimize crime rates in East Java. Data analysis was carried out by analyzing the Miles and Huberman model data which consisted of three stages, namely data reduction, data presentation (data display), and drawing or verifying conclusions. The results showed that the social policy strategy in minimizing the crime rate in East Java is to create a labor-intensive housing program and increase the expansion of higher education services so that it can produce graduates who are in accordance with the needs of the labor market, especially in remote rural areas. Obstacles that are considered to be able to interfere with the implementation of social policy strategies in an effort to minimize the crime rate in East Java include: social conflicts that cannot be estimated when and where they occur, conflicts and competition in the community, the number of people in East Java which is relatively high and there are economic inequalities in several areas of East Javanese society.